ANALISIS SIFAT MEKANIS MATERIAL DUCTILE MELALUI UJI TARIK DAN BENDING - Ilham Hidayathullah; Rifelino Rifelino; Andril Arafat; Febri Prasetya (Jurnal Vokasi Mekanika (VoMek), 2024)
Ductile materials are often used in industry. Apart from its affordable price, its ductile and flexible properties make it easy to shape and apply in the structural industry. It is not uncommon for these materials to be chosen for their high utility. However, each ductile material has its own characteristics that differ from one material to another, ductile material means a material that has the ability to be forged or stretched due to its high level of flexibility. You can use tensile tests and bending tests. This tensile test and bending test aims to determine the hardness and ductility of ductile materials. The ductile materials used in this study are aluminum and brass. The tensile test is carried out using a UTM machine using 3 test pieces that have the same shape and size for each material. The first material is aluminum. The tensile test results on aluminum material obtained an average of 355.78 N/mm2. Meanwhile, the tensile test on brass material obtained an average of 442.28 N/mm2. Furthermore, for bending tests on aluminum and brass materials. This test uses the three point bending method and with 3 test objects of the same shape and size. The results of bending tests on aluminum material obtained an average of 1,562.961 N/mm2. As for the brass material, the average bending test value is 2,466.664 N/mm2. So it can be concluded that the tensile test